Effect of unilateral nephrectomy on urinary angiotensinogen levels in living kidney donors: 1 year follow-up study. (October 2017) - Kendi Celebi, Zeynep; Peker, Ahmet; Kutlay, Sim; Kocak, Senem; Tuzuner, Acar; Erturk, Sehsuvar; Keven, Kenan; Sengul, Sule
Background: Urinary angiotensinogen (uAGT) has recently been proposed as a marker of kidney injury and activated intrarenal renin–angiotensin system. We investigated the effects of living donor nephrectomy on uAGT levels, blood pressure, estimated glomerular filtration rate, proteinuria and compensatory hypertrophy in the remaining kidney of living kidney donors. Methods: Twenty living kidney donors were included in the study and followed for 1 year. uAGT levels were measured with enzyme-linked immunosorbent assay preoperatively and postoperatively at the 15th day, 1, 6 and 12 months. Results: Four donors were excluded from the study due to lack of data. The mean baseline estimated glomerular filtration rate was 98 ± 15 ml/min/1.73 m². Serum creatinine, uAGT/creatinine, uAGT/protein levels were higher and estimated glomerular filtration rate was lower than baseline values at all time periods. Urinary protein/creatinine levels increased after donor nephrectomy, but after 6 months they returned to baseline values. Renal volume increased after nephrectomy, but these changes did not show any correlation with uAGT/creatinine, uAGT/protein, estimated glomerular filtration rate or systolic/diastolic blood pressures. uAGT/creatinine at 6 months and urinary protein/creatinine ratio at 12 months showed a positive correlation ( P =0.008, r =0.639). Conclusion: After donor nephrectomy, increasing uAGT levels can be the result of activation of the intrarenal renin–angiotensin system affecting the compensatory changes in the remaining kidney. The long-term effects of increased uAGT levels on the remaining kidney should be examined more closely in future studies.